Anthropometric indices, body function, and physical fitness reference values for Tibetan ethnic children aged 6–17 residing at 3,650 meters above sea level - Ma, Xiaowei; Mao, Yong; Wang, Jian; Zewangzhandui,; Wang, Xiaomei (Frontiers in Nutrition, 2022)
Objectives: It is known that high altitude influences the growth metrics of high-altitude residents. Using a WHO-recommended standard, the research aimed to establish growth and development reference values for children of Tibetan ethnicity between the ages of 6 and 17 years old. Methods: The measurements took place in Jomda County, Tibet with an average altitude of 3650 meters above sea level. A total of 3955 observations (1932 boys and 2023 girls) were utilized to model the centile estimations. Included in the measurements are height, weight, body mass index, heart rate, blood pressure, forced lung capacity, sit and reach, and standing long jump. The measurements were modeled using the generalized additive models for location, scale, and shape (GAMLSS). Models were fitted with suitable distributions and locally smoothed using the P-spline for each GAMLSS hyper-parameter. Using the smallest Schwarz Bayesian criterion, the optimal model for each measurement was selected. After model adjustment, centile estimations were calculated for each model. Results: Compared to the height reference values at the 50th percentile for multi-ethnic Chinese children residing at low altitudes, Tibetan ethnic children exhibit apparent stunted growth. In terms of forced vital capacity, it is remarkable that Tibetan ethnic children lag behind multi-ethnic Chinese children residing at low altitudes. Heart rate and blood pressure regulation are generally normal. Centile estimations are provided in this article and tabulated centiles (1p, 3p, 5p, 15p, 25p, 50p, 75p, 85p, 95p, 97p, 99p) in Chinese, Tibetic, and English are openly available in FigShare (DOI: 10.6084/m9.figshare.20898196.v1). Conclusion: This study established the first GAMLSS based growth and development reference values for Tibetan ethnic children aged 6 to 17. These reference values have numerous clinical and scientific applications. We offer Chinese policymakers with practical initiatives to further enhance the health of Tibetan ethnic children.